STRATEGI PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) BERBASIS PERTANIAN DI KABUPATEN SUMBAWA BARAT - Nursan, Muhammad; Utama FR, Aeko Fria (Jurnal Social Economic of Agriculture, 2019)
One of the efforts to develop village economic in West Sumbawa Regency is to establish and develop Village Owned Enterprise (Bumdes) based on agriculture. The purpose of this research is to find out internal and external factors of Bumdes based on agriculture; and formulating strategies for developing Bumdes based on agriculture in West Sumbawa Regency. This research was conducted in West Sumbawa Regency. 40 respondents were selected by purposive sampling. This research method is survey method. The instrument validity test was carried out with the Pearson Product Moment correlation technique, and for the reliability test with the Cronbach Alpha formula. Data collected were analysed using SWOT analysis. The results show that internal factors in the form of the main strength of Bumdes based on agriculture is the business managed by Bumdes serving the basic needs of community, while the main weakness is the capacity of managers managing Bumdes still lacking, and the absence of marketing networks. For external factors, the main opportunities of Bumdes based on agriculture are the support of local and central government regulations, the area and potential of agriculture can be developed optimally as well as the development and expansion of agricultural businesse, while the main threats of Bumdes are the lack of community participation in Bumdes activities. Results of  SWOT analysis, the strategy Bumdes based on agriculture in West Sumbawa Regency can be done using the W-O (Weakness-opportunity) strategy, which is a strategy that minimizes the weaknesses that are owned to seize opportunities. Keywords: Analysis. SWOT, Agriculture, Development Strategy, Village Owned Enterprise, West Sumbawa Regency